(untitled) (World Bulletin of Management and Law, 2022)
This study mainly aims to investigate the impact of monetary development on economic activity in Iraq. As a model (ARDL)and test kranger (Causality Test) to determine the direction of causal relationships between the variables of monetary development (M1, M2, M3 .) and variableGross domestic productat prices ongoing.In addition, the study used the dynamic standard model with appropriate slowdown periods to measure the impact of monetary variables in the short and long term on growtheconomic,The results are in agreement with the theoryeconomic,The test results showedCranger CausalityThere is a causal relationship between monetary development variables and real GDP. Also, the results of the dynamic model (ARDL) showed that there are positive effects of monetary variables on real GDP